Reverse Numerical Simulation of Kinetic Parameters from Acidic Copper Hull Cell Deposition. Issue 5 (1st May 2022) - Kovácsovics, I.; Patzelt, T.; Herrmann, J.; Bund, A.
Abstract : Hull cell depositions are industrially used to monitor electrolytes and study the influence of additives. By combining the Hull cell deposition and a numerical simulation based on the boundary element method via a curve-fitting approach allows to obtain kinetic parameters (e.g. transfer coefficient, exchange current density) and assessing the effects of additives without losing the visual information and the opportunity to get the structural and physical properties of the metal deposition (reverse determination). In an acidic copper electrolyte, an additive based on polyethylene glycol decreases the effective exchange current density, j 0, e f f by up to two orders of magnitude, while the transfer coefficient is hardly influenced. By adding another additive based on bis-(3-sulfopropyl)disulphide, the effect is counteracted and j 0, eff increases in dependence on the ratio of both additives. The combined approach enables obtaining more information about visual and structural effects and the deposition kinetics from one experimental analysis.